Return to sports after COVID-19 infection: Do we have to worry about myocarditis? - Schellhorn, P.; Klingel, K.; Burgstahler, C. (European Heart Journal, 2020)
Current coronavirus disease (COVID-19) has grown into a pandemic crisis of major health and economic importance. An infection with severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) is known to cause severe respiratory symptoms up to an acute respiratory distress syndrome (ARDS), but also often involves the cardiovascular system,1,2 which is associated with increased mortality.3 The highest mortality rates were observed in patients with underlying cardiovascular disease and co-existing elevated cardiac troponin levels.4 In particular, elevated serum levels of cardiac troponin and inflammatory biomarkers (i.e. interleukin-6 and serum ferritin) were characteristic for cases with severe illness and non-survivors.4-8 This high inflammatory burden in COVID-19, described as a hyperinflammatory response, is considered to be co-responsible for development of ARDS, vascular inflammation, myocarditis, and myocarditis-related cardiac events, e.g. arrhythmias.6,7 However, many individuals have only mild or no symptoms despite being infected.